VD_FINDINFO HC / 2013 / 651 vom 10. Oktober 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, ALLOCATION FAMILIALE, MINIMUM VITAL | 176 CC, 179 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)